Esophageal Squamous Cell Carcinoma Presenting with Streptococcus intermedius Cerebral Abscess - Rabih Nayfe; Mustafa S. Ascha; Esther H. Rehmus (Hindawi Limited, 2017)
Background. Cerebral abscess is caused by inoculation of an organism into the brain parenchyma from a site distant from the central nervous system. Streptococcus intermedius (S. intermedius) is a commensal organism that is normally present in the aerodigestive tract and was reported to be the cause of brain abscesses after esophageal dilatation or upper endoscopy. Case Presentation. We report the case of a 53-year-old female who presented with hematemesis and melena followed by left-sided weakness. Initially, her hemiplegia was found to be secondary to a right thalamic brain abscess caused by S. intermedius. Investigations led to the diagnosis of a mid-esophageal squamous cell carcinoma. We hypothesize that the cause of the abscess with this bacterium that naturally resides in the digestive tract and oral cavity is secondary to hematogenous spread from breach in the mucosal integrity from ulceration due to the cancer. Conclusion. To our knowledge, our case is the first in the literature to describe a brain abscess caused by S. intermedius in association with a previously undiagnosed esophageal squamous cell carcinoma without any prior esophageal intervention.